2019
DOI: 10.3390/su11051246
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Precursors in Oncology Nurses: A Preliminary Cross-Sectional Study with a Systemic Organizational Analysis

Abstract: Burnout negatively affects nurses’ health and performance. Healthcare managers have an ethical duty to create healthy organizations that reduce burnout, especially within critical settings such as oncology. The aim of this study was twofold: (1) to measure the presence of nurses’ burnout to formulate organizational strategies to prevent the syndrome onset, and (2) to evaluate the effect of recent organizational changes on the burnout phenomenon. A descriptive, cross-sectional design supported by a systemic org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
2
17
0
1
Order By: Relevance
“…This result requires special attention as previous studies showed that emotional distress is frequently associated with suboptimal patient care and professional inefficiencies along with long-lasting effect on health professionals' health status (Panagioti et al, 2018). On the other hand, healthcare workers seemed to be still capable of finding some gratification from their job, as only a rather small amount of them appeared to have low levels of Personal Gratification, which may be considered as a relevant protective factor for the professionals' mental health, as demonstrated in previous studies (Bonetti et al, 2019;Zwack and Schweitzer, 2013).…”
Section: Discussionsupporting
confidence: 51%
“…This result requires special attention as previous studies showed that emotional distress is frequently associated with suboptimal patient care and professional inefficiencies along with long-lasting effect on health professionals' health status (Panagioti et al, 2018). On the other hand, healthcare workers seemed to be still capable of finding some gratification from their job, as only a rather small amount of them appeared to have low levels of Personal Gratification, which may be considered as a relevant protective factor for the professionals' mental health, as demonstrated in previous studies (Bonetti et al, 2019;Zwack and Schweitzer, 2013).…”
Section: Discussionsupporting
confidence: 51%
“…Regarding burnout levels, in contrast to Barello et al (2020) that reported a large percentage of Italian healthcare professionals with high scores in at least one of the MBI domains, in our study, only 20% of the sample had high levels of emotional exhaustion and 7% had high levels of depersonalization, whereas 44% of the sample showed high levels of personal accomplishment. HCWs still seemed to be capable of finding some gratification from their jobs, which may be considered as a relevant protective factor for the professionals' mental health, as demonstrated in previous studies (Zwack and Schweitzer, 2013;Bonetti et al, 2019). These results can be seen as part of controversial results of the impact of being in an epicenter.…”
Section: Discussionmentioning
confidence: 61%
“…Education Shortages of academically qualified staff Aiken et al, 2013;Nardi & Gyurko, 2013;Auerbach et al, 2015;Sawaengdee et al, 2016;Haddad & Toney-Butler, 2018 Nursing profession Specifics of nursing profession Evans & Frank, 2003;Dietrich Leurer et al, 2007;Pillay, 2009;Aiken et al, 2013;Sawaengdee et al, 2016;Squires et al, 2017;Haddad & Toney-Butler, 2018 Human resource HRM and working environment Newman et al, 2001;management Aboshaiqah, 2016;Squires et al, 2017;Bonetti et al, 2019 Scholars outline important specifics of the nursing profession, such as high turnover, the inequitable distribution of the workforce (Sawaengdee et al, 2016) in terms of women's dominance and relevant sociocultural factors (Squires et al, 2017), and the willingness to travel and commute to the workplace (Janež et al, 2018;Drobne & Bogataj, 2013. While financial incentives manage to reduce turnover to a degree, a large number of baby-boomer nurses will retire soon, and new nursing graduates will not be able to close that gap due to the limited increase in their numbers (Auerbach et al, 2015).…”
Section: Facet Description Authorsmentioning
confidence: 99%
“…How one models entrances and exits in the nursing profession is an important theoretical and empirical question. Because of turnovers, one can witness burnouts and identify a lack of organisational strategies (Bonetti et al, 2019). We test and extend this theory by developing a model that enables investigating the factors related to nurse employment dynamics.…”
Section: Introductionmentioning
confidence: 99%